Role And Influence Of Local Governments In Poland On Creating The Social Policy Of The State, In Scope Of Social Assistance - Wojciech Glac (European Scientific Journal, ESJ, 2016)
Te social policy constitutes fundamental instrument of the state in realization of the tasks concerning protection of the citizens from the social risks, supporting social development, along with the simultaneous respecting the rules of social justice. Local governments in Poland,which originally are supposed to function close to a citizen, according to the decentralization’s rules in their scope of competence they realize broad catalogue of the tasks in the field of the social policy. At the same time, the bodies of the local governments seem to be proper when influencing on and creating principles of the social policy in the state, in the range of their competence, taking into consideration the needs and local determinants.